Aligning organizational culture and operations strategy to improve innovation outcomes: An integrated perspective in organizational management. Issue 2 (11th March 2019) - Wu, Li-Fan; Huang, Ing-Chung; Huang, Wei-Chang; Du, Pey-Lan
Abstract : Purpose: Innovation is a key factor in assessing organizational success. The purpose of this paper is to examine how the organizational culture and operations strategy impact organizational innovation. It explores the influence of various combinations of organizational cultures and operations strategies on a firm's ability to innovate both in process and product. Design/methodology/approach: A conceptual model is developed which attempts to explain how the reciprocal and dynamic interactive relationship between organizational culture and operations strategy and innovation is structured. In total, 233 valid questionnaires were collected from 17 small- and medium-sized enterprises (SMEs) in Taiwan. Structural equation modeling was used to investigate the direction and strengths of the relationships and develop a comprehensive picture to illustrate the drivers of successful innovation. Findings: The analysis and conclusions confirm the suitability of Culture–Strategy–Innovation Model and the detailed results demonstrate that a combination of innovative organizational culture and flexibility-oriented operations strategy has the strongest influence on a firm's innovation process thereby improving their innovative organizational outcomes. Practical implications: Although based on Taiwanese manufacturing industries these results provide useful insights for manufacturing industries in general. In alternative contexts, the combination of different dimensions of culture and strategy can be expected to cause different levels of success in innovation. This study provides robust evidence to explain the organizational climate needed to guide the innovative and flexibility considerations needed for SMEs in the manufacturing industry. Originality/value: This is an empirical study which specifically investigates the activities of SMEs in the metal/plastic manufacturing industry in Taiwan and in particular examines organizational culture, operations strategies and innovation. The research model proposed and confirmed offers a new multi-dimensional structure of culture and strategy linked with their various related dynamic interrelationships and the drivers that impact organizational innovation.